Maternal supplementation of twin bearing ewes with calcium and magnesium alters immune status and weight gain of their lambs. (June 2020) - Ataollahi, Forough; Friend, Michael; McGrath, Shawn; Dutton, Geoff; Peters, Andrew; Bhanugopan, Marie
Highlights: Pregnant ewes have an impaired immune system at around one week prior to lambing and at lambing time. Calcium and magnesium supplementation improved antioxidant capacity of growing lambs. Calcium and magnesium supplementation improved leukocyte functions in newborn lambs. Calcium and magnesium supplementation improved live weight gain of lambs from birth to 4 weeks after birth. Abstract: This study investigated the effect of supplementation of ewes with calcium (Ca) and magnesium (Mg) in late gestation and early lactation on the plasma mineral concentration, hormone profile and immunity responses of ewes and their lambs. Twin bearing ewes were allocated between four dietary treatment groups ( n  = 11 per treatment): control (0.33% DM Ca and 0.28% DM Mg); high Ca (0.72% DM Ca and 0.28% DM Mg); high Mg (0.33% DM Ca, 0.48% DM Mg); and high Ca+Mg (0.66% DM Ca and 0.47% DM Mg), offered as part of a whole ration. Ewes were fed the treatment supplement from around one month prior to lambing to one month after lactation. Blood and urine samples were collected at seven time-points: weekly starting at 5 weeks prior to lambing; within 12 h post lambing (+12 h); and then at fortnightly intervals at 2 week (+2 W) and at 4 week (+4 W) post lambing. Colostrum/milk samples from ewes and blood samples from lambs were collected at +12 h, +2 W and +4 W. Live weight of lambs were measured at +12 h, +2 W and +4 W. The plasma concentration of PTH, 1, 25(OH)2 D3 and 25(OH)D3 was lowest at +2 W ( P  ≤ 0.002). Ewes from the Ca+Mg group had the lowest mean concentration of 1, 25(OH)2 D3 than the other groups ( P  = 0.005). Magnesium supplementation improved the plasma Mg concentration over time in ewes ( P  <  0.001) and lambs from the control group had lower plasma Mg concentration compared to the treatment groups at +4 W ( P  = 0.001). Oxidative burst response in lambs supplemented with Ca tended to be greater at +4 W than the other groups at the same time point ( P  = 0.051) and Mg supplementation increased total antioxidant capacity (TAC) concentration in lambs ( P  = 0.040). The average daily weight gain of lambs was 204 g/lamb/d for the Ca group, 207 g/lamb/d for the Mg group, 245 g/lamb/d for the Ca+Mg group which were greater than the control group (148 g/lamb/d) ( P  < 0.001). Despite the normal concentration of Ca and Mg in the plasma, supplementation of ewes with Ca and Mg from one month prior to lambing to one month post lambing improved TAC concentration and weight gain in lambs.